Diagnosis of swine influenza - Janke, BH (Journal of Swine Health and Production, 2000)
In recent years, swine influenza has become recognized as asignificant contributor to the porcine respiratory disease complex(PRDC), which is causing severe problems in many swine operations.Infection with swine influenza virus (SIV) is not always clinicallyevident and diagnostic tests often must be conducted to detectthe presence of the virus, especially in cases of enzootic infection.A variety of assays are available to detect SIV or the antibodyinduced by the virus. The appearance of antigenically variantH1N1 strains and, more recently, of new H3N2 subtype strains inswine populations in the United States has raised questions aboutcross-protection and about our ability to detect the new strainswith currently available diagnostic tests. In this review, wepresent information to update the reader on the methods availableto detect swine influenza, to differentiate among SIV strains,and on the optimum use of these tests.
Keywords: swine; swine influenza virus; diagnosis; H3N2 subtype